2022
DOI: 10.1016/j.cub.2021.11.055
|View full text |Cite
|
Sign up to set email alerts
|

Retinal horizontal cells use different synaptic sites for global feedforward and local feedback signaling

Abstract: Retinal horizontal cells use different synaptic sites for global feedforward and local feedback signalingHighlights d Horizontal cells show segments of increased diameter (bulbs) on their dendrites d Bulbs contact both bipolar cells and other horizontal cells d Bulb contacts are GABAergic synapses d Horizontal cells could provide global signals to bipolar cells at bulbs

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 77 publications
0
23
0
Order By: Relevance
“…Implications for the adoption of GEVIs for in vivo voltage recordings In this study, we report on JEDI-2P, a new voltage indicator that addresses a critical need in neuroscience: the noninvasive recording of rapid voltage transients for extended durations and in deep cortical layers. We evaluated JEDI-2P for reporting voltage dynamics in different cell types, subcellular locations, and animal models (also see Behrens et al, 2022). We also demonstrated that JEDI-2P could record voltage responses using distinct 2PM microscopy methods.…”
Section: Discussionmentioning
confidence: 95%
“…Implications for the adoption of GEVIs for in vivo voltage recordings In this study, we report on JEDI-2P, a new voltage indicator that addresses a critical need in neuroscience: the noninvasive recording of rapid voltage transients for extended durations and in deep cortical layers. We evaluated JEDI-2P for reporting voltage dynamics in different cell types, subcellular locations, and animal models (also see Behrens et al, 2022). We also demonstrated that JEDI-2P could record voltage responses using distinct 2PM microscopy methods.…”
Section: Discussionmentioning
confidence: 95%
“…UV-On) could simultaneously receive sign-preserving inputs from H1 and/or H2 HCs, which themselves carry a sign-preserving long-wavelength biased signal 7 . In zebrafish, the presence of direct inputs from HCs to BCs has not been observed; however, the concept is tentatively supported by the anatomical presence HC-BC contacts in mice 52 . Third, zebrafish might have ACs that use fast neurotransmitters other than GABA and/or glycine, which presumably continue to function throughout our pharmacological interventions.…”
Section: Discussionmentioning
confidence: 99%
“…BCs that express ionotropic glutamate receptors (BCs: 1(ab), 2, 3(a,b), 4) are responsible for forming the OFF signaling routes [ 11 , 12 ], whereas those that utilize metabotropic glutamate receptors (5(a–d), 6, 7, 8/9) are responsible for conveying ON signals [ 11 ]. The first synaptic layer of the retina is also equipped with HCs that express inhibitory GABA as a transmitter and signal laterally, thereby providing feedback and feedforward inhibition to PRs and BCs, respectively [ 13 ]. This inhibition serves mainly as a spatial filter and thus forms the basis for an inhibitory surround receptive field of downstream retinal neurons and thus contrast detection for vision [ 14 ].…”
Section: The Wiring Of the Mammalian Retinamentioning
confidence: 99%
“…HCs are GABA-expressing inhibitory cells in the outer retina. They receive glutamatergic excitation from photoreceptors and provide feedback inhibition to photoreceptors and feedforward inhibition to BCs ( Figure 4 ) [ 13 ]. It has been shown that the inhibitory feedback is established through ephaptic mechanisms whose morphological substrate is provided by pore-forming hemichannels [ 59 , 60 , 61 ].…”
Section: Circuit Elements That Contribute To Response Transiencementioning
confidence: 99%